Ամրոց-բնակատեղի «Խոխանաբերդ» Վիմական արձանագրություններ Խաղբակյանների մասին - Սարգսյան, Սլավա (ԱրՊՀ հրատ․)
Находясь в ущелье реки Хаченагет, крепость Хоханаберд сыграла значительную роль при нашествии арабов, турок-сельджуков, монголов и других завоевателей. На территории крепости имеется много историко-культурных памятиков с еще не изученными древними надписями. Последние представляют большой интерес для изучения истории рода Хахбакянов. Being in the ravine of the Khachenaget River, the fortress of Khokhanaberd played a significant role during the invasions of the Arabs, Turk-Seljuks, Mongols and other invaders. In the territory of the fortress there are a lot of historical and cultural monuments with ancient inscriptions, which have not been studied yet. The latter are of great interest for the study of the family history of Khakhbakyans.
Keywords: Արցախ; Աշխարհագրություն; Վիմագրություն